Longitudinal associations between bone and adipose tissue biochemical markers with bone mineralization in boys during puberty. Issue 1 (December 2016) - Vaitkeviciute, Donvina; Lätt, Evelin; Mäestu, Jarek; Jürimäe, Toivo; Saar, Meeli; Purge, Priit; Maasalu, Katre; Jürimäe, Jaak
Abstract Background We investigated longitudinal relationships between the biochemical markers of bone and adipose tissue with bone mineral content (BMC), bone mineral density (BMD), moderate-to-vigorous physical activity (MVPA) and sedentary time (SED) in pubertal boys. Methods Ninety-six boys (11.9 ± 0.6 years old) were measured at baseline, after 12 and 24 months. Body composition (fat mass [FM], lean body mass [LBM]), and whole body (WB), lumbar spine (LS) and femoral neck (FN) BMD and BMC were assessed. Additionally, serum leptin, adiponectin, osteocalcin (OC) and C-terminal telopeptide of type I collagen (CTX) were measured. Results OC had a strong longitudinal inverse effect on changes in WB_BMD (p < 0.001) and LS_BMD (p = 0.021), while CTX had an inverse effect only on changes in FN_BMD (p = 0.011). Leptin had an inverse effect on changes in WB_BMC/WB_BMD (p = 0.001), FN_BMD (p = 0.002) and LS_BMD (p = 0.001). MVPA showed a longitudinal inverse effect on changes in leptin (p = 0.030), however no longitudinal effect of SED to biochemical markers of bone and adipose tissue was found. Conclusions Bone metabolism markers have negative effect on bone mineral accrual during puberty. Increases in MVPA affect leptin, suggesting a positive link of MVPA through leptin metabolism on increases in bone mineralization during puberty.